2013
DOI: 10.1021/ef400684f
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Changes of the Aerosol Composition and Concentration during Different Burning Phases of Wood Combustion

Abstract: The presented wood combustion emission study employing a logwood stove showed that four burning phases of different aerosol compositions and different amounts of emitted particulate matter (PM) occurred during a combustion batch. As a novel approach, in this study, the burning phases were defined by chemical changes in the aerosol gas phase during combustion, instead of being linked to predefined time periods or the amount of PM emissions. This deeper view into the aerosol chemistry of the different burning ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
68
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 43 publications
9
68
0
3
Order By: Relevance
“…The major ion was CO C , in contrast to typical atmospheric OM where the CO C and CO C 2 signals are similar (Aiken et al 2008). Overall, this highly oxygenated POM mass spectrum is consistent with previous AMS studies on beech wood combusted in logwood stoves (Weimer et al 2008;Heringa et al 2011;Elsasser et al 2013). Although this study is the first wood-stove study to identify and quantify CO C , two others (Grieshop et al 2009b;Eriksson et al 2014) have reported elevated signals at m/z 28 (most likely CO C or C 2 H C 4 ) and other biomass-burning studies (Ortega et al 2013) have observed similar patterns.…”
Section: Om Mass Spectrumsupporting
confidence: 88%
See 1 more Smart Citation
“…The major ion was CO C , in contrast to typical atmospheric OM where the CO C and CO C 2 signals are similar (Aiken et al 2008). Overall, this highly oxygenated POM mass spectrum is consistent with previous AMS studies on beech wood combusted in logwood stoves (Weimer et al 2008;Heringa et al 2011;Elsasser et al 2013). Although this study is the first wood-stove study to identify and quantify CO C , two others (Grieshop et al 2009b;Eriksson et al 2014) have reported elevated signals at m/z 28 (most likely CO C or C 2 H C 4 ) and other biomass-burning studies (Ortega et al 2013) have observed similar patterns.…”
Section: Om Mass Spectrumsupporting
confidence: 88%
“…As discussed in the SI (Section S1.1), negligible amounts of C 2 H C 4 were produced by our sample. It is worth emphasizing that overloaded stoves or poor combustion conditions may create considerably different POM to that observed here, with less oxygenation and significant PAH content (Elsasser et al 2013;Eriksson et al 2014). Figure 5b shows the OOM mass spectrum, which contained less CO C and more CO C 2 than the POM spectrum.…”
Section: Om Mass Spectrummentioning
confidence: 79%
“…Zhang et al, 2007), or during source studies (e.g. Elsasser et al, 2013;Timko et al, 2014;Corbin et al, 2015a).…”
Section: Influence On Positive Matrix Factorization Resultsmentioning
confidence: 99%
“…Christian et al, 2007;Yokelson et al, 2008). Others, including Schneider et al (2006), Weimer et al (2008) and Elsasser et al (2013) have investigated the chemical composition of BBA emissions in real time during biomass combustion in the laboratory. Attempts to compile all available measurements of emission factors for a number of different species, both gaseous and particulate, have been carried out by Andreae and Merlet (2001) and more recently by Akagi et al (2011).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the standard approach in many such studies has been to consider only average emission factors from an entire combustion event, which can mask significant changes in emissions that take place throughout combustion. Nonetheless, some recent studies have been carried out, which consider real-time particulate emissions under more controlled conditions, including Alfarra et al (2007) and Elsasser et al (2013).…”
Section: Introductionmentioning
confidence: 99%